Implementation of Kurikulum Merdeka for Physical Education Subjects in Sekolah Penggerak at the Junior High School Level in Temanggung Regency - Indra Setiawan; Endang Sri Hanani; Bambang Priyono (STKIP Muhammadiyah Kuningan, 2023)
This study aimed to analyze the implementation of PJOK learning with the independent curriculum at the SMP Pengerator School in Temanggung Regency. The research method used is a qualitative approach. Methods of data collection using observation, interviews, and document search. The research subjects were principals, PJOK teachers, and students at nine junior-level driving schools in the Temanggung district. The study results found that PJOK teachers at nine driving schools had already carried out PJOK learning plans with an independent curriculum and had implemented PJOK learning with an independent curriculum. The assessment carried out has also been carried out by the independent curriculum. From the results above, it can be concluded that PJOK teachers in 9 driving schools at the Temanggung district junior high school level have carried out learning with an independent curriculum.